Intelligence Analysis: Delays in the Formation of the Crime of Sexual Violence Law and It’s Derivative Regulations - Zainuna Rahayu; Maria Puspitasari; Stepi Anriani (Ridwan Institute, 2023)
This research is motivated by the increase in sexual violence numbers, both against women and other vulnerable groups. Sexual violence requires legislative intervention which in its process faces obstacles because of the appearance of controversy. The controversy affects the slow process of approval of the law and its derivative rules. Using the concept of strategic intelligence analysis, this research was carried out. Qualitative approach with descriptive type, research using document study and interviews as data collection techniques. Data suggests that reviewed strategic intelligence analysis fails due to factors of lack of knowledge about sexual violence and its implications, besides the concept of strategic intelligence analysis for mapping conflict and contesting actors has not been used in the policy formulation process. These weaknesses affect the extent to which the state budget is being used to allocate prolonged regulatory formulation, in addition to affecting the social and psychological costs to the victims and existing support systems, including law enforcement and victim protection. Recommendations to all stakeholders, first of all relating to the intelligence function of information sharing, enhancing intelligence capacity especially at the knowledge level, as well as encouraging enhanced cooperation and collaboration among actors to jointly strive for Indonesia to be free from sexual violence.